Seing Black Race, Crime, and Visual Processing. (article). - Eberhardt, Jennifer L.
Using police officers and undergraduates as participants, the authors investigated the influence of stereotypic associations on visual processing in 5 studies. Study 1 demonstrates that Black faces influence participants' ability to spontaneously detect degraded images of crime-relevant objects. Conversely, studies 2-4 demonstrate the activating abstract concepts (i.e., crime and basketball) induces attentional biasis toward Black male faces. Moreover, these processing biases may be related to the degree to which a social group member is physically representative of the social group (Study 4-5). These studies, taken together, suggest that some associations between social groups and concepts are bidirectional and operate as visual tuning devices -producing shifts perception and attention of a sort likely to influence decision making and behavior . -- (from the author)
Keywords: Psychology-Periodicals.